SOCIAL RELATIONSHIPS OF THE MAIN CHARACTERS IN ROWLING’S FANTASTIC BEAST AND WHERE TO FIND THEM - Meinawati, Euis; Setianingrum, Herlin Widasiwi; Jimmi, Jimmi; Winata, Eggi (Research And Innovation In Language Learning (RILL), 2019)
The purpose of this research was to know the social relationships through Sorokin's theory. This research was done through a film titled Fantastic Beast and Where to Find Them which was released in 2016. The data were taken from the utterances of the characters’ dialogue through documentation, the process of watching, and post watching the film. The method of research used a qualitative descriptive method. The results of the study indicated that: (1.) the types of social relationships are social interaction phenomena and non-social interaction phenomena, (2.) From the seven data about a social relationship, three data are about social interaction phenomena:  by human in friendship, by human in ethnicity, and social interaction phenomenon in helping the economy, (3.) using Tsapeli's theory, the sub-chapters of the causes and effects are also successfully identified.